MODERN POSSIBILITIES OF SPECKLE TRACKING ECHOCARDIOGRAPHY IN CLINICAL PRACTICE - V. S. Nikiforov; I. V. Nikishchenkova (Рациональная фармакотерапия в кардиологии, 2017)
Speckle-tracking echocardiography is promising modern technique for evaluation of structural and functional changes in the myocardium. It evaluates the indicator of global longitudinal myocardial deformation, which is more sensitive than ejection fraction to early changes of left ventricular contractility. The diagnostic capabilities of speckle tracking echocardiography are reflected in clinical recommendations and consensus statements of European Society of Cardiology (ESC), European Association of Cardiovascular Imaging (EACVI) and American Society of Echocardiography (ASE). The aim of this paper is describe basic principles of speckle tracking echocardiography and clinical applications of this new technology. Attention is paid to the use of speckle tracking echocardiography in such heart pathologies as heart failure, coronary heart disease and myocardial infarction, left ventricular hypertrophy in arterial hypertension, hypertrophic cardiomyopathy and amyloidosis of the heart, valvular heart disease, constrictive pericarditis and cancer therapy-induced cardiotoxicity.